用于辅助确定对象的器官中的动脉供血区域的功能细分的装置 (2025)
本发明的目的是提供允许辅助用户确定改进的患者121的器官中的动脉供血区域的细分的装置110。图像提供单元111提供对象的器官的图像。测地距离图生成单元113基于解剖图像来生成针对感兴趣区域的测地距离图，其中，测地距离图的体素由从预定种子到相应体素的累积路径代价给出，并且其中，路径代价是基于代价函数来确定的，代价函数考虑分别基于图像确定的血管度滤波器响应和/或造影剂密度。测地距离图提供单元114将测地距离图提供给用户和/或进行进一步处理以确定动脉供血区域。 It is an object of the invention to provide an apparatus 110 that allows for assisting a user in determining an improved subdivision into arterial feeding regions in an organ of a patient 121. An image providing unit 111 provides an image of an organ of a subject. A geodesic distance map generation unit 113 generates a geodesic distance map for a region of interest based on the anatomical image, wherein a voxel of the geodesic distance map is given by a cumulated path cost from a predetermined seed to the respective voxel and wherein the path cost is determined based on a cost function taking into account a vesselness filter response and/or a contrast agent density determined, respectively, based on the image. A geodesic distance map providing unit 114 provides the geodesic distance